Layanan Pesan Pendek untuk Pembangunan Pertanian di Kabupaten Karawang - Haris Tri Wibowo; Djuara P Lubis; Resfa Fitri (Institut Pertanian Bogor, 2015)
Application of information and communication technology (ICTs)currently has integrated with agricultural development. Information and communication technologies (ICTs) such as mobile phones have been used in rural development activities. LISA is a groundbreaking program that aims to provide an integrated agricultural services include agricultural tips services, the interactive dialogue, and iteration financial services based on mobile phone short message service. The main objective of this study to determine the effectiveness of LISA as agricultural information dissemination media based short message service role in agricultural development. The purposes of the study were 1) to analyze the exposure of LISA user; 2) to analyze the relationship between user characteristics and external factors against LISA’ exposure; 3) to analyze the relationship between LISA exposure against the effectiveness of communication; and 4) to analyze the relationship between interaction with other information sources against the effectiveness of communication. The sample selection method used in the study was multiple stage sampling. The sample included 100 LISA user in Karawang District. The data analysis was carried out using the descriptive correlational analysis and SEMpls. The result showed that the land area cultivated respondent significantly affect LISA’ exposure. External factors do not significantly affect the LISA exposure. LISA exposure significantly affect the effectiveness of communication. Interactions with other information sources does not significantly influence the effectiveness of communication.Keywords: short message service, LISA exposure, the effectiveness of communication